2020
DOI: 10.3390/agronomy10121908
|View full text |Cite
|
Sign up to set email alerts
|

Yield, Agronomic and Forage Quality Traits of Different Quinoa (Chenopodium quinoa Willd.) Genotypes in Northeast China

Abstract: Quinoa (Chenopodium quinoa Willd.) grain is well known as a source of nutritious human food, but the nutritional properties of quinoa as animal fodder has not been well explored. Fifteen quinoa accessions were assessed for grain and forage yields, and morphological and quality traits during anthesis and grain filling, with the aim of selecting superior genotypes for greater production and quality traits that are well adapted to northeastern China. Variations were significant among the tested genotypes for all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…The total number of shoots was recorded by counting all branches emerging from the main stem at different node positions, including the basal branches. Although plant biomass was not measured at the end of the experiment, a previous study in C. quinoa showed that the number of shoots is positively correlated with final biomass (Shah et al, 2020). Moreover, both traits, plant height and number of shoots, have been demonstrated to be susceptible to salinity in halophyte plants, including C. quinoa (Vasquez et al, 2006;Hussain et al, 2020;Jaramillo Roman et al, 2020).…”
Section: Morphological Measurementsmentioning
confidence: 97%
“…The total number of shoots was recorded by counting all branches emerging from the main stem at different node positions, including the basal branches. Although plant biomass was not measured at the end of the experiment, a previous study in C. quinoa showed that the number of shoots is positively correlated with final biomass (Shah et al, 2020). Moreover, both traits, plant height and number of shoots, have been demonstrated to be susceptible to salinity in halophyte plants, including C. quinoa (Vasquez et al, 2006;Hussain et al, 2020;Jaramillo Roman et al, 2020).…”
Section: Morphological Measurementsmentioning
confidence: 97%
“…In this context, quinoa offers an excellent alternative crop to ensure food and nutrition security in hot drylands such as the MENA region. Quinoa has a potential use for animal feeding, especially under arid conditions where grain and plant maturity are sometimes difficult to obtain 83 . In fact, the strategy of developing salt-tolerant plants and halophytes as alternative crops to be grown in marginal environments of this region is very important insofar as the major cereal crops are progressively failing to produce satisfied yield under salinity and scarce water resources 21 27 .…”
Section: Introductionmentioning
confidence: 99%
“…After seed harvesting, there is potential for quinoa growers to market straw a forage crop [24][25][26]. Generally, genotypes with thick stems, more branches, and moderate plant height producing higher biomass are ideal for fodder and genotypes with compact inflorescence are ideal for grain purpose [27]. Presently, some quinoa lines with high nutritional profile, biomass, and low saponin contents have been evaluated for fodder purposes [unpublished data].…”
Section: Developments In Quinoa Researchmentioning
confidence: 99%